Heart rate variability mediates the association between polycyclic aromatic hydrocarbons exposure and atherosclerotic cardiovascular disease risk in coke oven workers. (August 2019) - Yang, Liangle; Guo, Wenting; Zeng, Dan; Ma, Lin; Lai, Xuefeng; Fang, Qin; Guo, Huan; Zhang, Xiaomin
Abstract: Polycyclic aromatic hydrocarbons (PAHs) metabolites was related to heart rate variability (HRV) reduction and atherosclerotic cardiovascular disease (ASCVD), and ASCVD was also affected by HRV. However, the mediating role of HRV in the association between PAHs exposure and ASCVD risk was largely unknown. We aimed to investigate whether the relation of PAHs exposure with ASCVD risk was mediated by HRV among coke oven workers. A total of 1100 subjects with complete data were qualified in the current study. We measured 12 urinary PAHs metabolites by gas chromatography-mass spectrometry (GC-MS) and HRV indices by 3-channel digital Holter monitors. The associations between urinary PAHs metabolites, HRV indices, and ASCVD risk were explored using generalized linear models or multivariate logistic regression models. A mediation analysis was conducted to examine the role of HRV on the association between PAHs exposure and ASCVD risk. We found that urinary 1-hydroxynaphthalene (1-OHNa), 2-OHNa, and total PAH metabolites (ΣOH-PAH) were dose-responsive associated with increased risk of ASCVD. Compared with lowest quartile, the adjusted odds ratio (OR) for ASCVD risk in the highest quartile were 2.36 for 1-OHNa, 6.58 for 2-OHNa, and 1.60 for ΣOH-PAH (all P trend <0.05). In addition, significant dose-dependent relationships were found across 2-OHNa quartiles with decreasing HRV indices, which in turn, were positively associated with elevated risk of ASCVD (all P trend <0.05). Mediation analyses indicated that HRV mediate 2.7%–4.3% of the association between 2-OHNa exposure and higher ASCVD risk. Our data suggested that occupational exposure to PAHs may increase ASCVD risk, which was partially mediated by HRV. Graphical abstract: Image 1 Highlights: Urinary 1-OHNa, 2-OHNa, and ΣOH-PAH were related to increased ASCVD risk. Urinary 2-OHNa was inversely related to 5 HRV indices. Decreasing HRV indices were positively associated with elevated risk of ASCVD. HRV mediated 2.7%–4.3% of the association between 2-OHNa exposure and ASCVD risk.